Жіночі поясні амулети черняхівської культури - Бобровська, О.В. (Археологія, 1999)
У статті розглядаються в типологічному, хронологічному, економічному, соціальному та етно-графічному аспектах жіночі поясні амулети черняхівської культури. В женском уборе черняховской культуры широкое распространение получили комплекты амулетов, состоящие из костяных пирамидальных подвесок, раковин Cypraea panterina и Bolinus brandaris семейства Myricidae, а также зубов животных. Дата комплексов с поясными амулетами — середина — третья четверть IV в. Их попадание в ареал Черняховской культуры обусловлено стабилизацией морской торговли после завершения «готских» войн, а также, вероятно, присутствием среди ее носителей потомков западных сарматов. The sets of amulets containing the shells Cypraea pantarina and Bolinus brandaris, bone pyramidal pendants and fangs. The sets are dated from the mid/third quarter of the fourth century. Their appearance within the Cherniakhiv’s territory is quite explainable in terms of stabilization of sea trade in the aftermath of the «Goths’ wars»; the fact that there were some descendants of the Western Sarmatians within the Cherniakhiv community also contributes to the explanation.